Spreminjanje naselbinskih vzorcev: definiranje nukleacije - disperzije - Fikfak, Alenka (AR. Arhitektura, raziskave, 2004)
Settlements are varied and they experience constant changes that occur both in form and relations to neighbouring ones. The latter evolves from instability of settlement patterns - nucleation changing into dispersal and vice versa. Dispersal relies on ideas of individuality, while nucleation stems from those pertaining to community. The used statistical method "nearest neighbourhood analysis" is presented in the definition of "oscillation" between the two phenomena (and quest for physical explanations for nucleation- dispersal). The relation between built form and surrounding environment affects numerous settlement patterns, from which evolve definitions of various phenomena, above all for the relationship form pattern.In the countryside the village territory is a settlement pattern's influential area and the basis for researching processes on the level of particular settlements.
Keywords: prostorsko urejanje; rural area; podeželje; naselbine; naselbinski prostor; naselbinska kultura; architecture; arhitektura